Concrete compressive strength development when polyethylene terephthalate partially replaces sand / Muhammad Redza Rosman and Norishahaini Mohamed Ishak - Muhammad Redza, Rosman; Norishahaini, Mohamed Ishak (2015)
The diminution of sand and waste build-ups are two problems often faced today. This research was initialised to investigate the suitability of sand replacement with poly ethylene terephthalate (P.E.T) and also to evaluate the strength development of concrete where sand is replaced with P.E.T.In this research, a total of 40 numbers of 100mm x100mm x 100mm concrete cubes were made for the control specimen, 10%, 20%, 30% and 50% P.E.T replacement, half of which were for the 0.52 water/cement (w/c) ratio and the other half for 0.64w/c ratio. Two cubes of each replacement percentages were cured at three days and the other two at 28 days. The strength imposed at the point of failure marks their individual maximum strength, where they were recorded and analysed.